The Relationship of Mother's Knowledge and Attitude with Growingflowing to Development at Novi Lintas Timur's Midwife Clinic Panyabungan District, Kota Regency Mandailing Natal Year 2021 - Helmi Wardah Nasution (Institute of Computer Science (IOCS), 2022)
According to the World Health Organization (WHO), the Infant Mortality Rate (IMR) is the first health indicator in determining the health status of children. RISKESDAS 2018 data for the Mandailing Natal area in the Proportion of monitoring growth in the last 12 months in children 0-59 months by Regency/City in North Sumatra province, namely those who weigh 231 people (47.96%) with a frequency of < 8 times 70 ,70%, > 8 times 22.20%, and body length/height was measured with a frequency of 1 time 14% and > 2 times 76.32%. This type of research is descriptive correlational. The sampling technique of this research is a total sampling of 35 people. Research results, Chi-Square test analysis is known that the significant value of p value is 0.027. Because the p-value is smaller than 0.05 (0.027 <0.05) then Ha is accepted so that in this study there is a significant relationship between knowledge and attitudes of mothers with growth and development of toddlers at the Novi Midwife Clinic in 2020. These results prove that mothers who have Good knowledge tends to have an accepting and positive attitude towards toddler growth and development. It is hoped that research sites, institutions, respondents and further researchers will pay attention to the growth and development of toddlers, so that they can achieve optimal results. According to the World Health Organization (WHO), the Infant Mortality Rate (IMR) is the first health indicator in determining the health status of children. RISKESDAS 2018 data for the Mandailing Natal area in the Proportion of monitoring growth in the last 12 months in children 0-59 months by Regency/City in North Sumatra province, namely those who weigh 231 people (47.96%) with a frequency of < 8 times 70 ,70%, > 8 times 22.20%, and body length/height was measured with a frequency of 1 time 14% and > 2 times 76.32%. This type of research is descriptive correlational. The sampling technique of this research is a total sampling of 35 people. Research results, Chi-Square test analysis is known that the significant value of p value is 0.027. Because the p-value is smaller than 0.05 (0.027 <0.05) then Ha is accepted so that in this study there is a significant relationship between knowledge and attitudes of mothers with growth and development of toddlers at the Novi Midwife Clinic in 2020. These results prove that mothers who have Good knowledge tends to have an accepting and positive attitude towards toddler growth and development. It is hoped that research sites, institutions, respondents and further researchers will pay attention to the growth and development of toddlers, so that they can achieve optimal results.